Assessment of Violence Against Medical Staff in Prince Salman Hospital in Al Riyadh City, Case Study - Alotaibi, Ahlam Melfi (Journal of Economic, Administrative and Legal Sciences, 2018)
The current study aims at assessing violent prevalence experienced and / or witnessed by medical staff at work, and determining whether there is a relationship between the prevalence of violence which the staff of Prince Salman Hospital has experienced and/or witnessed and the demographic factors. Descriptive and analytical case study method was used to gather information at Prince Salman Hospital. The health care staff of the hospital is the sample. All of them were asked to do the questionnaire. Results indicate that most of the staff are subjected to a variety of violence, at least, once a day. The statistical analysis shows that physical violence rates are between 27.7% and 30.4 %, verbal violence rates are between 41.1% and 41.1%, and sexual harassment rates are between 11.6 % and 19.6. In addition, results refer that there is a relationship between physical violence, age, and the workgroup. Whereas, there is no relationships between physical violence and sexual intends. in regarding with verbal violence, there is a relationship with different elements of age, marital status, and workgroup. Furthermore, there are no relationships between sexual harassments and marital status and workgroup. The present study conclusions that there are increasing numbers of violent states at the Prince Salman Hospital in Al-riyadh. So, it recommends that some procedures must be done to help the staff to handle violent actions, to develop the policies of reporting events, to increase security and community awareness with the phenomenon of violence.